Intimate Partner Violence: Views and Perspectives of Young Women at Maputo-city Secondary Schools, Mozambique - Maria Suzana Bata Maguele; Myra Taylor; Nelisiwe Khuzwayo (SAGE Open, 2023)
Intimate partner violence (IPV) among young women is of serious concern due to the early age of occurrence. This study explored young women’s views about IPV in Maputo City, Mozambique. An explorative, qualitative study design was employed using purposive sampling. The themes were developed in line with the socio-ecological model and the data were analyzed using a thematic content approach. Four themes emerged: (1) Individual level, related to the knowledge of young women about IPV; (2) Relationship level, related to the influence of friends; (3) Community level, related to the religious beliefs; and (4) Societal level, related to factors promoting acceptance of IPV. There is need for an integrated approach to address the individual, relationship, community and societal concerns about IPV among young women in Mozambique to improve skills to challenge the dominant male norms and enhance their autonomy to manage and end violent relationships.